Olympic and international level sports coaches` experiences of stressors, appraisals, and coping - Didymus, F. F. (Qualitative Research in Sport, Exercise and Health, 2017)
The aim of this study was to use the cognitive-motivational-relational theory (CMRT) of stress and emotions as a lens to explore psychological stress with Olympic and international level sports coaches. In particular, the study aimed to explore situational properties of stressors and coaches` appraisals to address voids in the published literature. Guided by my constructionist epistemological position that contains traces of post-positivism and my relativist view of reality, I conducted semi-structured interviews with six women and nine men. I applied abductive logic during latent thematic analyses to organise and analyse the data. The findings suggest that the coaches experienced many stressors that related to 10 themes (e.g. athlete concerns, performance) and that these stressors were underpinned by seven situational properties (e.g. ambiguity, imminence, novelty). The coaches reported challenge and threat appraisals and, to a lesser extent, benefit and harm/loss appraisals. The ways of coping that were discussed with the coaches related to seven families of coping (e.g. dyadic coping, support seeking) that each play a different role in adaptive processes. Collectively, the findings shed new light on the explanatory potential of situational properties and appraisals and go some way towards understanding coaches` diverse experiences. The CMRT was a useful framework for understanding high level coaches` stress transactions and, thus, could be used in future research with this unique population. Coaches, practitioners, and researchers should attend to the ways that coaches appraise and cope with stressors to facilitate their adaptation to the potentially stressful nature of coaching at the highest levels